Higher Education Henchmen: Vicarious bullying and underrepresented populations - Hollis, Leah P. (Advances in Social Sciences Research Journal, 2017)
This study is an original examination of the overlooked phenomenon of vicarious bullying in higher education. While researchers have brought attention to direct bullying, vicarious bullying—which results when a third party acts as the aggressor or henchman—can also create destructive environments that lead to employee disengagement and turnover. The findings reported in this analysis were obtained through a meta-analysis of 317 American institutions of higher education, thus including both four-year and two-year colleges. The purpose of this analysis was to consider the frequency of vicarious bullying as reported by the study participants. The participants invited to engage the instrument were from 317 colleges and universities. Of these study respondents 35% of them (n = 197) reported being the target of vicarious bullying. Participants from underrepresented backgrounds involving race, gender, and sexual orientation also reported vicarious bullying with higher frequency than the 35% frequency reported from the general sample.